Strangulated Hernia Can Be a Risk Factor of Seroma following Laparoscopic Transabdominal Preperitoneal Repair. (26th August 2018) - Matsumoto, Ryu; Nagahisa, Yoshio; Hashida, Kazuki; Yokota, Mitsuru; Okabe, Michio; Kawamoto, Kazuyuki
Abstract : Purposes . Seroma is a postoperative complication following laparoscopic transabdominal preperitoneal repair (TAPP) for inguinal hernioplasty. Seroma naturally resolves in most cases, but it can lead to an increased amount of visits to the outpatient clinic and can result in anxiety of the patient. Local inflammation of the inguinal area is etiology of seroma formation. Strangulated hernia involves severe inguinal pain and can lead to severe inflammation and subsequent seroma. There have been no reports demonstrating the links of seroma and strangulated hernia. This study aimed to retrospectively evaluate the risk of seroma after TAPP and to identify the association between strangulated hernia and seroma. Methods . We treated 300 inguinal hernias by TAPP between 2013 and 2016 at Kurashiki Central Hospital. We used the Chi-square test. Factors significant in each association were further examined using multiple subsequent logistic regressions. Results . A total of 222 hernias were eligible for analysis. The incidence of seroma was 11% (n=25). There were nine cases of strangulated hernias, and three (33%) resulted in seroma. The ratio of strangulated hernia of seroma group is significantly high (p<0.03). Multiple subsequent logistic regressions showed that strangulated hernia was associated with a significantly increased risk for seroma formation (p = 0.023; OR 6.564; 95% CI 1.29-33.3). Conclusion . This study shows that strangulated hernia can be a risk factor in seroma formation. This risk should be incorporated into a management plan of TAPP for strangulated hernia, with careful consideration of patients' concerns.